O livro do desassossego e as máscaras de Deus em Fernando Pessoa - Araujo, Maria Claudia (2009)
This research investigates lhe masks of God in lhe work of Fernando Pessoa, andespecially its various manifestations in lhe ambit heteronomy and polyphonicof lhe poetic Pessoa. The corpus used is lhe Book of Unquietness, written overlhe life of Pessoa, signed by lhe semi-heteronyms Bernardo Soares, and dialoguewith lhe personalities of his main heteronymous: Alberto Caeiro, lhe objectivistpoet, Alvaro de Campos, lhe poet subjectivist, and Ricardo Reis, lhe classical poet. Further dialogue with lhe Book, not just lhe characters of lhe heteronymous, but also lhe major poems by Alberto Caeiro, among which stands out lhe poem VIII of The Keeper of Flack af Sheep. The Triumphal Lyrical of Alvaro de Campos and lhe classic Iyrical of Ricardo Reis also supports lhe dialogue with lhe Book of Unquietness. Alberto Caeiro, Alvaro de Campos and RicardoReis have an immanent conception of divinity, while lhe look of Bernardo Soares and lhe own Fernando Pessoa is predominantly mystic and transcendentalist. In this theatrical static, lhe heteronomous characters, diverted, lhe dream narrative fragmented, as well' as lhe process of literary production of FernandoPessoa, feed a sei of multiple masks that point to lhe polyphony and lhe different faces of lhe divinity in Pessoa's work